The Gambia : Staff Report for the 2013 Article IV Consultation; Informational Annex; Press Release on the Executive Board Discussion; and Statement by the Executive Director for The Gambia. (IMF Staff Country Reports; Country Report ;, 2013)
This IMF Staff Report for the 2013 Article IV Consultation presents economic development and policies of Tthe Gambia. The IMF report shows that Tthe Gambia's economy is picking up slowly from the past drought conditions. The Gambian Programme for Accelerated Growth and Employment (PAGE) emphasizes fiscal adjustment, together with infrastructure investment and structural reforms to support inclusive growth. Fiscal adjustment is needed to ease the heavy debt burden, arising mainly from domestic debt. Execution of the PAGE, supported by commitments from development partners, would help reduce poverty, especially in rural areas, given a strong focus on agriculture.